2011
DOI: 10.1103/physreve.83.061109
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of excitability for the FitzHugh-Nagumo model via a stochastic sensitivity function technique

Abstract: We study excitability phenomena for the stochastically forced FitzHugh-Nagumo system modeling a neural activity. Noise-induced changes in the dynamics of this model can be explained by the high stochastic sensitivity of its attractors. Computational methods based on the stochastic sensitivity functions technique are suggested for the analysis of these attractors. Our method allows us to construct confidence ellipses and estimate a threshold value of a noise intensity corresponding to the neuron excitement. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 32 publications
0
25
0
4
Order By: Relevance
“…As predicted by the SR scheme (see also [12]), it was shown that the oscillation of the FHN neuron becomes more closely correlated with the subthreshold periodic input current at some optimal level of noise intensity. The stochastic analysis of the FHN neuron and other neuron models has been extensively studied in recent years with various types of noises, multistability, and even how SR can be controlled; see, for example, [13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…As predicted by the SR scheme (see also [12]), it was shown that the oscillation of the FHN neuron becomes more closely correlated with the subthreshold periodic input current at some optimal level of noise intensity. The stochastic analysis of the FHN neuron and other neuron models has been extensively studied in recent years with various types of noises, multistability, and even how SR can be controlled; see, for example, [13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Поэтому в настоящее время развиваются подходы, позволяющие найти аппроксимации или асимптотики решений уравнения ФПК. Для систем с малыми случайными возмущениями могут быть использованы метод квазипотенциала [Вентцель, Фрейдлин, 1979;Dembo, Zeitouni, 1995] и техника функ-ций стохастической чувствительности [Башкирцева, Ряшко, 2001;Bashkirtseva, Ryashko, 2004;Bashkirtseva, Ryashko, 2011].…”
Section: Introductionunclassified
“…Therefore, various asymptotics and approximations are developed [22][23][24]. For the approximation of KFP solutions, a well-known quasipotential method [15,16] and a stochastic sensitivity function (SSF) technique [17][18][19]25] can be applied.…”
Section: Appendixmentioning
confidence: 99%
“…However, a direct usage of this equation is very difficult technically even in simple situations, therefore various asymptotics and approximations were developed. For an approximation of KFP solutions, a well-known quasipotential method [15,16] and a stochastic sensitivity function technique [17,18] can be used.…”
Section: Introductionmentioning
confidence: 99%